2019
DOI: 10.1186/s13071-019-3490-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a tri-allelic PCR assay for screening Vgsc-L1014F kdr mutations associated with pyrethroid and organochlorine resistance in the mosquito Culex quinquefasciatus

Abstract: Background Culex quinquefasciatus has a widespread distribution across tropical and sub-tropical regions, and plays an important role in the transmission of vector-borne diseases of public health importance, including lymphatic filariasis (LF) and multiple arboviruses. Increased resistance to insecticides threatens the efficacy and sustainability of insecticide-based anti-vector interventions which mitigate the burden of mosquito transmitted diseases in endemic regions. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, the primers published by Chen et al (2010) are 19-23 bp, while the primers in this study are longer, 24-29 bp, for increasing specificity [27]. Martins et al (2019) developed an engineered-tail allele-specific-PCR (ETAS-PCR) for detecting L1014F in Cx. quinquefasciatus [28].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the primers published by Chen et al (2010) are 19-23 bp, while the primers in this study are longer, 24-29 bp, for increasing specificity [27]. Martins et al (2019) developed an engineered-tail allele-specific-PCR (ETAS-PCR) for detecting L1014F in Cx. quinquefasciatus [28].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 80%
“…Martins et al (2019) developed an engineered-tail allele-specific-PCR (ETAS-PCR) for detecting L1014F in Cx. quinquefasciatus [28]. ETAS-PCR diagnostics relies on the design of different tail sequences incorporating an enzyme cutting site, each associated with a specific kdr-like mutations.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Currently, many reports have shown that the larval and adult stages of Cx. quinquefasciatus sre resistant to synthetic insecticides ( Lopes et al., 2019 ; Atyame et al., 2019 ; Nachaiwieng et al., 2021 ) because of knockdown resistance ( kdr) gene mutations, such as L1014F, G1195S ace-1, and the cytochrome P450 genes CYP9J45, CYP9J40, and CYP6AA7 ( Delannay et al., 2018 ; Silva Martins et al., 2019 ; Maestre-Serrano et al., 2020 ; Yoshimizu et al., 2020 ). These kdr gene mutations of Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, more cost-effective and rapid single-tube assays, e.g. multiplex PCR and tri-allelic PCR [18, 29], should be taken into account urgently. In general, the degree of resistance and the frequency of susceptible alleles detected by AS-PCR were almost the same as those by sequencing, meaning AS-PCR can accurately reflect the resistance levels of a given Ae.…”
Section: Discussionmentioning
confidence: 99%